The Inference of Religious Education Methods in the Field of Beliefs Through the Nature of Religion in the Holy Quran - Mehrnaz Donboli; Khosrow Baqeri Noaparast; Sayyid Mohsen Mirbaqeri; Mahmoud Abaei Koupaei (آموزه‌های قرآنی)
Four important ways of religious education in the field of beliefs are inferred in this article through the nature of religion in the Holy Quran. We have examined two categories of “nature of religion” and “methods of religious education” for this purpose. All verses including the root of “د ـ ی ـ ن” (religion) have been investigated in order to properly understand the nature of religion in the Holy Quran. Then, we have benefited from the inference method to find the ways of religious education in the Holy Quran. In the inferential method, we have reached the “conclusion”, which is the method of religious education by using two premises, “normative” and “realistic”. The solutions of the Holy Quran to achieve the methods of religious education are explained in the following. For example, using the Scriptures directly to know the right actions is one of the solutions of the Holy Quran to reach the way of believing in the punishment of deeds. The achievement of religious education methods through discovering the nature of religion and explaining the purpose of education on the one hand and using the inferential method as a research method on the other hand is one of the innovations of this research. The achievements of this paper can be used to provide an educational theoretical model for formal and public education system.